DETERMINATION OF PART SPECIFICATION AND CRITICAL PAR FOR FOOD PACKAGE IMPROVEMENT AT MSME AE JAYA BATU BY USING QFD METHOD - Rika Amartha Wulandari; Yuswono Hadi (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2017)
MSME AE Jaya is a food industrial company which produces Bakpia. It is located in Jalan Samadi Batu City. Recently, AE Jaya markets its products in Batu and Malang city. During its marketing, it faces some difficulties and problems in selling the products. Such as it is not accepted in a particular supermarket or even in a souvenir shop. It is because the standard packaging of its bakpia is not fulfilled yet. Not only that, it is also because the packaging is less interesting and less hygienic. Due to this condition, therefore a research is needed. The research aims to identify consumers’ attributes, technical requirement attributes and critical part attributes in bakpia’s packaging that produces by AE Jaya. Those aspects could be very helpful in identifying or knowing some information about an interesting packaging design and how to make a good packaging which is appropriate with consumers needs. The method used in this research is called Quality Function Deployment. The researcher used the first phase and the second phase of QFD. Based on the analysis that has been conducted, there are 8 consumers’ attributes, 10 technical requirement attributes and 9 critical part attributes.